Sustainable groundwater development for improved agrarian livelihoods in Sub-Saharan Africa: a decadal update - Pavelic, Paul; Verma, Shilp; Villholth, Karen G. (Taylor and Francis, 2025)
In 2013, Water International published a two-part special issue, Identifying the barriers and pathways forward for expanding the use of groundwater for irrigation in Sub-Saharan Africa. In the issue, the authors – and the editors – highlighted the enormous opportunity presented by Sub-Saharan Africa’s groundwater resources to improve agricultural productivity and potential to lift millions of smallholder farmers out of poverty. Since then, a lot has changed in the domain of groundwater irrigation in Sub-Saharan Africa, although perhaps not quite as rapidly or as democratically spread as the authors of the special issue would have liked to witness. This decadal update revisits the 2013 papers and reviews the developments since to chart a way forward for sustainable, inclusive and effective development and governance of groundwater for irrigation in the region.